Beyond the Gag Reflex: Understanding Soft Palate Variations for Better Dental Care: Understanding Soft Palate Variations for Better Dental Care - Qamar, Khezran; Mumtaz, Maryam; Rafique, Muhammad Hammad; Yaqub, Khalid; Nazif, Ayema; Hamid, Tayyaba; Naeem, Sajid (Pakistan Journal of Health Sciences, 2025)
The gag reflex is a defense process to protect the airway from irritants. In a few patients, exaggerated reflexes jeopardize the dental treatment and compromise the dental procedures. Objectives: To evaluate the potential association of the severity of gag reflex with types of soft palate in patients attending to prosthodontic clinic and to find out the association within gender, age groups. Methods: A cross-sectional observational study included 250 patients of both genders who needed dentures, were selected. Gag reflex was checked by touching the anterior to posterior part of the maxilla and mandible with a dental mirror while taking impressions. Gag Reflex Index (GRI) was used for the assessment of gag response. The reaction of the patients was recorded on V grades. The types of soft palates were classified via house classification as I, II, and III. Results: The soft palate forms frequently observed were soft palate drop type I, 60.0% followed by type II, 31.6 % and 8.0 % patients had type III soft palate drop. The gag reflex grade V was 5.6 %, grade IV was 4.8 %, grade III was 8.4%, grade II was 22.0 % and grade I was 59.2%. The association of gag reflex grades with gender and types of soft palate drop was found to be significant, 0.02 and 0.00. However, with different age groups, insignificant results were obtained, p 0.07. Conclusions: The study concluded that the severity of gagging is found more in female patients and patients with type II and III soft palatal anatomy. Dentists need to evaluate different soft palatal types, especially when dealing with female patients needing prosthodontic treatment.